2016
DOI: 10.1016/j.conbuildmat.2016.02.156
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the performance of asphalt concretes modified by dry way with polymeric waste

Abstract: An asphalt concrete has been modified by adding four polymeric wastes: polyethylene (PE) from micronized containers, polypropylene (PP) from ground caps, polystyrene (PS) from hangers and rubber from end-of-life tyres (ELT). These polymeric wastes were selected according to their availability, homogeneity and economic criteria considering the big amount of material required to build a road. The dry method has been used to modify the bituminous mixture due to its simplicity and the possibility to be carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 15 publications
(17 reference statements)
0
45
0
Order By: Relevance
“…As previously mentioned, polyethylene is a plastomer that softens to flow when subjected to warming, and becomes solid and rigid when the temperature decreases. The melting point ranges between 110 and 120 • C for LDPE [23][24][25]; around 125 • C for LLDPE [26], and between 130 and 149 • C for HDPE [15,27,28]. Those temperatures are below the temperature range that is commonly used in the production of hot asphalt mixtures.…”
Section: Polyethylene (Pe)mentioning
confidence: 96%
See 1 more Smart Citation
“…As previously mentioned, polyethylene is a plastomer that softens to flow when subjected to warming, and becomes solid and rigid when the temperature decreases. The melting point ranges between 110 and 120 • C for LDPE [23][24][25]; around 125 • C for LLDPE [26], and between 130 and 149 • C for HDPE [15,27,28]. Those temperatures are below the temperature range that is commonly used in the production of hot asphalt mixtures.…”
Section: Polyethylene (Pe)mentioning
confidence: 96%
“…The dry method is simpler and it can be applied in any asphalt plant without major modifications. This favors the use of this modification technique, facilitating the employment of recycled polymers [14,15]. However, the majority of the published studies have preferred the use of Sustainability 2019, 11, 646 3 of 20 the wet process [11,16,17], as it leads to a larger degree of modification of the binder and; therefore, to a better use of the reclaimed polymers (RP) to improve its properties.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of sustainable development is to use natural resources in the most optimized way so that, environmental and socioeconomic issues are minimized [15][16][17]. In the past few years, studies regarding alternative environmental friendly materials in asphalt pavement to improve its mechanical properties have been conducted [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several literature studies and research related to CA and LDPE found that the asphalt mixture characteristics that use these materials still meet the requirements set by Bina Marga (2014) and AAPA (2004) [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%